2012
DOI: 10.1080/10926771.2012.639203
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Domestic Violence Exposure among a Community Sample of Adult Perpetrators: What Mediates the Connection?

Abstract: The association between childhood exposure to domestic violence and later intimate partner violence (IPV) perpetration in adulthood has been well established in the literature. However, the literature examining the factors of exposure that contribute to perpetration in adulthood is fraught with mixed findings, with some studies finding a direct link between childhood domestic violence exposure and later IPV perpetration and others ruling out a link after controlling for other contextual barriers such as commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
5
18
0
2
Order By: Relevance
“…The third key predictor in this study was family violence exposure earlier in life. Exposure to family violence during childhood is one of the most frequently recognized risk factors of IPVAW perpetration (Capaldi, Knoble, Shortt, & Kim, 2012;Fleming et al, 2015;Gracia, Rodríguez, Martín-Fernández, & Lila, 2017;Mbilinyi et al, 2012;Ruddle, Pina & Vasquez, 2017). Our results underline the importance of this key predictor also in IPVAW offender recidivism (see also, Fowler, Cantos, & Miller, 2016).…”
Section: Article In Presssupporting
confidence: 56%
“…The third key predictor in this study was family violence exposure earlier in life. Exposure to family violence during childhood is one of the most frequently recognized risk factors of IPVAW perpetration (Capaldi, Knoble, Shortt, & Kim, 2012;Fleming et al, 2015;Gracia, Rodríguez, Martín-Fernández, & Lila, 2017;Mbilinyi et al, 2012;Ruddle, Pina & Vasquez, 2017). Our results underline the importance of this key predictor also in IPVAW offender recidivism (see also, Fowler, Cantos, & Miller, 2016).…”
Section: Article In Presssupporting
confidence: 56%
“…distorted cognitions about relationships, hostile attitudes and beliefs) (e.g. Capaldi et al, 2012;Costa et al, 2015;Eckhardt & Cane, 2014;Ernst et al, 2007;Howard et al, 2010;Mbilinyi et al, 2012;Murrell, Christoff, & Henning, 2007;Roehl & Guertin, 2014;Stuart et al, 2013;Trevillion, Oram, Feder, & Howard, 2012;Whitfield et al, 2003). Among these factors, the exposure to DV during childhood has been one of the most prevalent predictors for DV perpetration (e.g.…”
Section: Predictors Of DV Perpetrationmentioning
confidence: 99%
“…Among these factors, the exposure to DV during childhood has been one of the most prevalent predictors for DV perpetration (e.g. Capaldi et al, 2012;Carpenter & Stacks, 2009;Mbilinyi et al, 2012;Milaniak & Widom, 2015;Whitfield et al, 2003).…”
Section: Predictors Of DV Perpetrationmentioning
confidence: 99%
“…This exposure to family violence encompasses both direct childhood maltreatment and witnessing interparental violence. Research has shown a general rate of CFV for batterer men that ranges from 20% to 76% (Delsol & Margolin, 2004;Fernández-Montalvo et al, 2012;Fernández-Montalvo et al, 2011;Lee et al, 2013;Mbilinyi et al, 2012). More specifically, the direct victimization percentages of batterer men range from 22% to 76%, and their witnessed violence percentages range from 20% to 54% (Delsol & Margolin, 2004;Fernández-Montalvo & Echeburúa, 1997).…”
mentioning
confidence: 99%